2021
DOI: 10.5194/wcd-2021-9
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mechanisms driving MJO teleconnection changes with warming in CMIP6

Abstract: Abstract. Teleconnections from the Madden-Julian Oscillation (MJO) are a key source of predictability of weather on the extended time scale of about 10–40 days. The MJO teleconnection is sensitive to a number of factors, including the mean state dry static stability, the mean flow, and the propagation and intensity characteristics of the MJO itself, which are traditionally difficult to separate across models. Each of these factors may evolve in response to increasing greenhouse gas emissions, which will impact… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…For example, Changes to the Rossby wave sources in the model clusters was not directly investigated here as only a small number of models had the required high‐frequency output available. However, other Northern Hemisphere‐focused studies have found that in terms of modifying the strength and pathways of existing teleconnections, the changes in the background flow (as examined here) play a much larger role than direct changes to the Rossby wave source (Wang et al., 2022), but these also contribute more strongly to inter‐model uncertainty (Jenney et al., 2021). As mentioned above, changes in La Niña frequency (a major driver of change and variability in the Rossby wave source), and which would be expected to increase high pressure to the east of New Zealand, were not found to be robust to suggest that changes in the background zonal flow is likely the more dominant driver.…”
Section: Resultsmentioning
confidence: 77%
“…For example, Changes to the Rossby wave sources in the model clusters was not directly investigated here as only a small number of models had the required high‐frequency output available. However, other Northern Hemisphere‐focused studies have found that in terms of modifying the strength and pathways of existing teleconnections, the changes in the background flow (as examined here) play a much larger role than direct changes to the Rossby wave source (Wang et al., 2022), but these also contribute more strongly to inter‐model uncertainty (Jenney et al., 2021). As mentioned above, changes in La Niña frequency (a major driver of change and variability in the Rossby wave source), and which would be expected to increase high pressure to the east of New Zealand, were not found to be robust to suggest that changes in the background zonal flow is likely the more dominant driver.…”
Section: Resultsmentioning
confidence: 77%